Vector-borne pathogens in dogs from the Republic of Kosovo - Betim Xhekaj; Edwin Kniha; Linda Wiesmüller; Ina Hoxha; Barbara Eigner; Jovana Stefanovska; Aleksandar Cvetkovikj; Kurtesh Sherifi; Hans-Peter Fuehrer (Parasites & Vectors)
Abstract Background Canine vector-borne pathogens (CVBP) are transmitted by arthropod vectors such as ticks, fleas, mosquitoes, and phlebotomine sand flies and are of global veterinary and medical importance. Dogs are important reservoir hosts, which may develop potentially life-threatening clinical signs. The Balkan area harbors diverse vector fauna and associated CVBPs, and data, particularly from the Republic of Kosovo, are scarce. Considering the high number of stray and privately owned dogs primarily kept outside, living in close contact with dogs might promote spillover of zoonotic pathogens to human populations. To combat these diseases, a One Health approach is required. Therefore, our study molecularly analyzed samples of dogs for CVBP. Methods Blood samples of 276 dogs originating from all seven districts of Kosovo collected from 2021 to 2022 were screened using polymerase chain reaction (PCR) and sequencing for a substantial set of pathogens, including Anaplasma spp., Babesia spp., Bartonella spp., Ehrlichia spp., Filarioidea, Hepatozoon spp., Mycoplasma spp., Rickettsia spp., and Trypanosoma spp. Prevalence rates were statistically assessed on the basis of various factors such as sex, breed, age, and district. Results In total, 150 (54.3%) dogs tested positive for at least one pathogen, comprising eight species of five genera. The most prevalent pathogens detected were Candidatus Mycoplasma haematoparvum (55; 19.9%), Hepatozoon canis (52; 18.8%), and Mycoplasma haemocanis (49; 17.8%). We also detected double (32; 11.6%) and triple (5; 1.8%) infections, with the latter involving combinations of Mycoplasma spp., Dirofilaria repens, Dirofilaria immitis, H. canis, or Babesia vulpes. In addition, prevalence rates were calculated and mapped by district. Of all included factors, significant prevalence differences were found for purebred/mixed breed dogs as well as between age groups. Conclusions This study provides the first comprehensive polymerase chain reaction (PCR)-based screening and detection of vector-borne pathogens in dogs from Kosovo and highlights the circulation of pathogens with high veterinary importance and zoonotic potential. Graphical Abstract